FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN HEPATITIS PADA IBU HAMIL - Nati Indriani, Putu Lusita; Anggraini, Helni; Handayani, Sri (JOURNAL OF MIDWIFERY SCIENCE, 2021)
Background :Hepatitis is one of the leading causes of death for women in the world. Objective:To find out the factors that influence the incidence of hepatitis in pregnant women. Methods:This type of research is a quantitative research, where the researcher observes the research subject and looks for data related to the researcher without giving treatment to the research subject. Quantitative research using cross sectional design.Results: The results of the analysis of the relationship between age statistical tests showed p value = 1.0, parity with p = 0.142, and socio-economic with p = 0.12, it can be concluded that there is no relationship, and the results of research on the relationship between education and p = 0.02, occupation with p=0.001, sources of information with p=0.009, and the role of health workers with p=0.00; Based on the results of this study, there is a relationship between education, occupation, sources of information and the role of health workers with maternal knowledge about hepatitis B. Conclusion: There is a significant relationship between Education, Occupation, Sources of Information and Role of Maternal Health Workers with maternal knowledge about Hepatitis B in pregnancy. Then there is no relationship between Age, Parity and Socio-Economic Mother with mother's knowledge about Hepatitis B in pregnancy. Keywords: Age, parity, socioeconomic, education, occupation, sources of information, and the role of health workers.